Climate change and the politicization of ESG in the US - Hilson, Chris (Frontiers in Political Science, 2024)
ESG, or environmental, social, and governance, is seen by some as an instrument to tackle climate change, and by others as a tool to allow investors to assess climate change risks and opportunities. It has been widely politicized in the US, where Republican critics have characterized it as an attempt by the liberal financial elite to impose a leftist decarbonizing mission on the US economy through an investment risk back door. The current paper explores the way in which ESG has become a, perhaps unlikely, object of politicization by the political right. In doing so, it analyses the meaning of politicization in an ESG context and the various forms it has taken, both discursive and substantive. The paper also seeks to explain why it is that ESG politicization has occurred at particular junctures and draws on political opportunity theory from social movement studies to account for this. It further examines various reactions to the politicization of ESG that have sought to depoliticize it.